Using Internet for Product Marketing - Nayeem, Jannatun (Asian Accounting and Auditing Advancement, 2015)
In this paper, we discuss product marketing using the Internet, particularly the use of the Internet for product promotion and new consumer processes. Internet advertising, virtual store fronts, and virtual communities are explained with examples and our views. We then present new consumer processes on the Internet and show how they enhance the fulfillment of the consumer purchase needs and also support interactive marketing. We discuss the challenges of measuring Web advertisements and close the chapter with a summary of our views on the Internet and marketing.